Burden and risk factors for gastrointestinal symptom distress in HIV patients in the modern antiretroviral era. Issue 2 (1st February 2017) - O'Neill, Tyler J.; Raboud, Janet M.; Tinmouth, Jill; Rourke, Sean B.; Gardner, Sandra; Cooper, Curtis; Rueda, Sergio; Hart, Trevor A.; Rachlis, Anita; Burchell, Ann N.
ABSTRACT: In the modern antiretroviral (ARV) era, there is limited knowledge about the prevalence and risk factors for HIV patient-reported gastrointestinal (GI) symptoms (diarrhoea/soft stool, nausea/vomiting, bloating/painful abdomen, loss of appetite, and weight loss/wasting) and distress. We prospectively analysed data (2007–2014) on distressing GI symptoms from the Ontario HIV Treatment Network Cohort Study, which follows people attending HIV clinics. Using generalized estimating equations with a logit link, we estimated the associations of psychosocial, demographic, behavioural, and clinical factors with each GI symptoms compared to asymptomatic and non-bothersome symptoms. Among 1532 included participants, 80.4% were male, mean age was 45 years, and 64.6% reported being men who have sex with men. Most were Caucasian (56.3%), a median time since HIV diagnosis of 9.8 years (interquartile range (IQR): 4.1–16.9), and 83.1% were on ARV. More than two-thirds (68.7% (95% confidence intervals (CI): 63.1% to 69.2%)) reported one or more symptoms with a median of 1.2 (IQR: 0–1.7). The proportion remained stable over time since HIV diagnosis and ARV initiation. Risk factors varied for multivariable models. A strong association with Centre for Epidemiologic Studies Depression scale scores of ≥23 was found for all symptoms. Adjusted odds ratios (95% CI) were 1.72 (1.39–2.12), 2.95 (2.33–3.72), 2.20 (1.81–2.68), 4.97 (3.99–6.19), and 2.98 (2.52–3.82) for diarrhoea, nausea/vomiting, bloating, loss of appetite, and weight loss, respectively. With the exception of bloating, odds were significantly lower for those on ARV containing integrase inhibitors and greater for patients reporting current cannabis use. GI symptoms in the modern ARV era are highly prevalent and may arise as a common pathway of distress in response to psychosocial vulnerabilities, regardless of the stage of diagnosis. These findings support the need for integrated approaches to address psychological and physical distress in HIV disease.